POWDERED BAMBOO SHOOT EXTRACTS ON THE GROWTH OF ANTHRACNOSE (COLLETOTRICHUM GLOEOSPORIOIDES) - Legarde, Girlie M; Abello, Nonna Fatima H; Pascual, Pet Roey L (Journal of Agriculture and Technology Management; Vol 23 No 2 (2020): Vol 23 No 2 (2020): Journal of Agriculture and Technology Management (JATM) Volume 23 July - December 2020 Issue, 2020)
Bamboo shoots are known to contain antifungicidal properties. This contains moderate dietary fiber, essential amino acids and other anti-inflammatory agents. The antimicrobial activity of crude methanolic extracts of thorn ( Bambusa blumeana Schultes f. ), golden ( Schizostachyum brachycladum ) and giant ( Dendrocalamus asper ) bamboos were investigated in this study. Equivalent amounts of each powdered sample of the bamboo shoot powder were soaked in methanol solvent and were filtered and evaporated. The extracts were spread over potato dextrose agar (PDA) medium under aseptic condition and incubated at 37 0 C. A completely randomized design (CRD), with three replications, was used in this experiment. The result showed that all bamboo shoot extracts showed highly significant anti-fungal activity resulting in zero growth (0) mm from 24 and 72 hours or equivalent to 100% inhibition as compared to the control that has observed fungal growth on 48 and 72 hours at 6.5±0.5SD mm and 8.63±0.71SD mm, respectively. Thus, the result showed that Bambusa blumeana Schultes f. , Schizostachyum brachycladum, and Dendrocalamus asper extracts have potential anti-fungal compounds. Hence, bamboo shoots are effective in combatting anthracnose and its major economic loss in several crops.